Sistem Pakar Untuk Mendiagnosa Penyakit Angular Cheilitis Menggunakan Metode Case Based Reasoning (CBR) - Rozi Eka Putri; Indra Kanedi; Yupianti Yupianti (Jurnal Media Infotama, 2024)
This research aims to create an expert system application to diagnose Angular Ceilitis using the Case Based Reasoning (CBR) method to get solutions and information easily and quickly about the disease. This research method uses the waterfall method which begins with the requirements, design, implementation, verification and maintenance stages. This expert system was created using the PHP programming language and MySQL database. The Case Based Reasoing method can be used as a solution in using an expert system to diagnose angular ceilitis. In its application, the Case Based Reasoing method can provide a percentage of angular ceilitis. So that users can use this expert system as an application that can provide assistance in the initial diagnosis of angular ceilitis.